2014
DOI: 10.1016/j.biopsych.2013.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Biomarkers Revisited: Integrative Profiling of Peripheral Samples for Psychiatric Research

Abstract: Peripheral samples, such as blood and skin, have been used for decades in psychiatric research as surrogates for central nervous system samples. Although the validity of the data obtained from peripheral samples has been questioned and other state-of-the-art techniques, such as human brain imaging, genomics, and induced pluripotent stem cells, seem to reduce the value of peripheral cells, accumulating evidence has suggested that revisiting peripheral samples is worthwhile. Here, we re-evaluate the utility of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 82 publications
1
55
0
Order By: Relevance
“…Sz is a psychiatric disorder and there have been great efforts to the study of potential neuronal and glial abnormalities that may provide the basis of the aetiology of the disorder. However, findings from such studies have not yet been translated into biomarkers that are practical in clinical use [4] because brain biopsies are not acceptable and neuroimaging techniques are expensive [5] and the results are inconclusive. Thus, in recent years, there has been search for bloodbased biomarkers for Sz as a valid alternative [5,6] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sz is a psychiatric disorder and there have been great efforts to the study of potential neuronal and glial abnormalities that may provide the basis of the aetiology of the disorder. However, findings from such studies have not yet been translated into biomarkers that are practical in clinical use [4] because brain biopsies are not acceptable and neuroimaging techniques are expensive [5] and the results are inconclusive. Thus, in recent years, there has been search for bloodbased biomarkers for Sz as a valid alternative [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…However, findings from such studies have not yet been translated into biomarkers that are practical in clinical use [4] because brain biopsies are not acceptable and neuroimaging techniques are expensive [5] and the results are inconclusive. Thus, in recent years, there has been search for bloodbased biomarkers for Sz as a valid alternative [5,6] . Bloodbased biomarkers are regarded as a feasible option because the dysregulation of gene expression, epigenetic patterns, protein quantities, metabolic and inflammatory molecules in peripheral blood have been shown to have distinct patterns in people with Sz [4,5,711] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 2, blood-based analysis account for the majority of such studies, especially with the analysis of serum and plasma, although blood cells' analysis is growing in interest ( Table 3) [74]. The rationale behind this is that, even if psychiatric disorders are brain diseases, its consequences can be detected throughout the entire body; and, most importantly, the access to fluids like blood is considerably easier than the access to the living brain or even to CSF.…”
Section: Biomarker Discovery In Peripheral Fluidsmentioning
confidence: 99%
“…It has been demonstrated that there are dynamic changes correlating changes in brain and blood and vice-versa [47,74], and, in the case of SCZ, some changes in hormones, cytokines or growth factors can be replicated both in brain and blood stream [74,76].…”
Section: Biomarker Discovery In Peripheral Fluidsmentioning
confidence: 99%